2011
DOI: 10.4269/ajtmh.2011.10-0544
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Onchocerciasis and Epilepsy in the Itwara Hyperendemic Focus, West Uganda: Controlling for Time and Intensity of Exposure

Abstract: In 38 pairs of epilepsy patients and controls matched for time and intensity of exposure to transmission of onchocerciasis, the presence of microfilariae in the skin of epilepsy patients was found insignificantly elevated compared with controls (odds ratio = 1.68; 95% confidence interval [CI] = 0.60–4.57; P = 0.31). This difference was more pronounced when detection of subcutaneous nodules was used as indication of infection with Onchocerca volvulus (odds ratio = 2.77; 95% CI = 0.92–8.33; P = 0.065). These fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 23 publications
4
33
0
Order By: Relevance
“…Out of these records, 16 articles, medical theses and abstracts representing 11 studies were found to include a control group for the investigation of a relationship between onchocerciasis and epilepsy [18], [20], [29]–[42]. Two records, each representing an additional eligible study [43], [44], and one unpublished congress abstract [45] containing relevant information about one of the above-mentioned studies were identified in other sources.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of these records, 16 articles, medical theses and abstracts representing 11 studies were found to include a control group for the investigation of a relationship between onchocerciasis and epilepsy [18], [20], [29]–[42]. Two records, each representing an additional eligible study [43], [44], and one unpublished congress abstract [45] containing relevant information about one of the above-mentioned studies were identified in other sources.…”
Section: Resultsmentioning
confidence: 99%
“…Among these studies, heterogeneity in ORs was significant (Cochrane's Q test: p<0.001) and yielded an I 2 value of 65.7%. Data on the prevalence of nodules in PWE and PWOE was provided in four studies [20], [39], [40], [44] from which we calculated a pooled OR of 1.74 (95%CI: 0.94–3.20, p = 0.076) (Table 2). Between-studies heterogeneity was not significant (p = 0.093) and I 2 was assessed as 53.3%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 This parish of 4,743 inhabitants is situated in the Itwara onchocerciasis focus, with a prevalence of microfilaria (mf) carriers ranging from 15% to 85% in the 10-20 years age group of its 13 villages in 1994. 11 A detailed description of the epidemiology of onchocerciasis and epilepsy in Kabende parish can be found in our previous publications, [11][12][13][14] and detailed maps of the entire Itwara focus are presented by Garms and others. 15 All patients who were registered in the survey underwent a thorough clinical assessment.…”
Section: Case Reportmentioning
confidence: 99%
“…Unfortunately, in this publication, the number of subcutaneous nodules was communicated only for the complete sample but not separately for patients and controls 4. In view of the intriguing consistency between the above-mentioned investigations from Cameroon2 and Uganda,3 it would be of interest to know the exact result of nodule palpations carried out in the Central African Republic by Druet-Cabanac and others 4…”
mentioning
confidence: 99%